Filosofia da educação a partir do diálogo entre analíticos e continentais - Viero, Catia Piccolo (2004)
The following dissertation procedes a hermeneutic inquiry concerning the different trends of Contemporary Philosophy, specifying the debates between Analytic and Continental Philosophy. It manifests itself about the possibilities of setting a new meaning for subject-matters such as Philosophy of Education and Philosophy of Brazilian Education belonging to the undergraduate course of teaching kept by the School of Education at the Federal University of Santa Maria. Here it is intended to question the content of the above mentioned curriculum subjects departing from a criticizing dialogue with some of the most advanced theoretical and methodological propositions present at the contemporary philosophic sphere. Having the starting point at the controversy between Jürgen Habermas and Richard Rorty, here is argued the possibility of communicative, pragmatic and hermeneutic proposit ions contribute to add a new meaning to philosophic studies in education, underlining the need of updating the languages employed by teaching activity, in accordance with the development of new ways to think education during an age marked by the transition from the conscience to the linguistic paradigm. The analysis tries to make feasible the upbringing of new horizons to the reinterpretation of rationalities generally taken as core ideas by educational circles.